Behavioral changes and acute toxicity to the freshwater shrimp Atyaephyra desmaresti millet (Decapoda : Natantia) from exposure to acid mine drainage - de Bisthoven, Luc Janssens
Short-term 48 h laboratory bioassays with water from an acid mine drainage (AMD: pH 3.3, 4.4, 5.0, 5.5, 6.4, control) and water from an arsenic containing reservoir were performed with the freshwater shrimp Atyaephyra desmaresti Millet, validated in situ and compared to acidified control water (ACID). Behaviour, mortality and time to death were monitored with the Multispecies Freshwater Biomonitor (MFB). The shrimps had equal 24 h-LC(50)s at pH 4 in AMD and ACID. However, after 48 h AMD proved more toxic (48 h-LC50 at pH 5.2) than ACID (48 h-LC50 at pH 4.5). Stress behaviour in AMD consisted at pH <= 6.4 of a pH-dependent decrease in activity, with disappearance of circadian rhythmicity, and at pH 4.4 a clear increase of ventilation. At pH 5.5 bioaccumulation of metals was higher and locomotion lower than at pH 5.0. In ACID, only at pH <= 4.4 locomotion became abated and arythmic. Locomotion in the field was equal or higher compared to the laboratory, whereas the ventilation was higher in the laboratory. A. desmaresti is a valuable species to be used in short term behavioural bioassays of AMD in Europe.